Multifunctional Green Infrastructure in Shrinking Cities: How Does Urban Shrinkage Affect Green Space Planning? - Olivia Lewis (2022)
Despite global urbanization, not all cities have increasing populations. While not homogenous, shrinking cities arguably have different opportunities and challenges for green space than growing cities. This article reports a structured content analysis to investigate how urban green space planning evolved in two case study cities: Buffalo (New York, US) and Porto (Portugal). These cities both underwent shrinkage and suburbanization but with very different green space planning histories. The concept of green infrastructure is used as a lens to analyze green space planning change, specifically focused on multifunctionality. The aim of investigating how objectives and priorities for planning green spaces change during a period of urban shrinkage, and particularly what functions these cities have assigned to green space, showed that, over time, green spaces were expected to produce more ecological functions in both cities, and, particularly in Buffalo, contribute to the economic and demographic outcomes of the city. Overall trends in green space planning appear to have played a role but we find shrinking cities may leverage green space to meet unique needs. These findings contribute to the literature by addressing how shrinkage affects not only vacant areas but also overall green space planning, as well as suggesting that general green space planning studies should consider demographic change as a relevant context factor.